Salt intake and the validity of a salt intake assessment system based on a 24-h dietary recall method in pregnant Japanese women. (18th August 2015) - Satoh, Michihiro; Tanno, Yumi; Hosaka, Miki; Metoki, Hirohito; Obara, Taku; Asayama, Kei; Hoshi, Kazuhiko; Suzuki, Masakuni; Mano, Nariyasu; Imai, Yutaka
Abstract: Background : Information regarding salt intake in pregnant women in Japan is limited. An electronic system for the assessment of salt intake using a 24-h dietary recall method has been developed in Japan. The objectives of the present study were to investigate salt intake in pregnant women and to compare the salt intake estimated by the electronic salt intake assessment system with that measured by 24-h urinary salt excretion (24-hUNaCl). Methods : Data were collected on 24-hUNaCl and salt intake estimated by the salt intake assessment system for 35 pregnant Japanese women at approximately 20 weeks of gestation. The adjusted 24-hUNaCl (24-hUNaCl/[the number of urinations during the examination day – the number of missing urine collections] × the number of urinations during the examination day, g/day) was used as a standard. Results : The mean adjusted 24-hUNaCl was 7.7 ± 2.5 g/day, and mean systolic/diastolic blood pressure values were 106.1 ± 8.6/62.8 ± 6.5 mmHg. The adjusted 24-hUNaCl was significantly correlated with the salt intake estimated by the salt intake assessment system ( r = 0.47, p = 0.004). Bland-Altman analysis showed no significant mean difference (adjusted 24-hUNaCl – salt intake estimated by the assessment system = −0.36 g/day, p = 0.4) and no significant proportional bias ( p = 0.1). Conclusion : These results suggest that pregnant women in Japan restrict their salt intake, at least when they are being examined for salt intake. They also suggest that repeated use of the described system may be useful in estimating salt intake in pregnant women.